Studi Populasi Owa Jawa (Hylobates moloch) di Lereng Gunung Slamet Jawa Tengah - Sri Wahyuni; Erie Kolya Nasution (Fakultas Biologi | Universitas Jenderal Soedirman, 2016)
Javanese Gibbon (Hylobates moloch) is the endemic primate species in Indonesia. IUCN - World Concervation has given this species an endangered status. The habitat Hylobates moloch’s were found at Slamet Mountain in Central Java. The study entitled